Light from Dark Matter : Hidden Dimensions, Supersymmetry, and Inert Higgs - Gustafsson, Michael (Stockholms universitet, Fysikum, 2008)
Recent observational achievements within cosmology and astrophysics have lead to a concordance model in which the energy content in our Universe is dominated by presumably fundamentally new and exotic ingredients – dark energy and dark matter. To reveal the nature of these ingredients is one of the greatest challenges in physics. The detection of a signal in gamma rays from dark matter annihilation would significantly contribute to revealing the nature of dark matter. This thesis presents derived imprints in gamma-ray spectra that could be expected from dark matter annihilation. In particular, dark matter particle candidates emerging in models with extra space dimensions, extending the standard model to be supersymmetric, and introducing an inert Higgs doublet are investigated. In all these scenarios dark matter annihilation induces sizeable and distinct signatures in their gamma-ray spectra. The predicted signals are in the form of monochromatic gamma-ray lines or a pronounced spectrum with a sharp cutoff at the dark matter particle’s mass. These signatures have no counterparts in the expected astrophysical background and are therefore well suited for dark matter searches. Furthermore, numerical simulations of galaxies are studied to learn how baryons, that is, stars and gas, affect the expected dark matter distribution inside disk galaxies such as the Milky Way. From regions of increased dark matter concentrations, annihilation signals are expected to be the strongest. Estimations of dark matter induced gamma-ray fluxes from such regions are presented. The types of dark matter signals presented in this thesis will be searched for with existing and future gamma-ray telescopes. Finally, a claimed detection of dark matter annihilation into gamma rays is discussed and found to be unconvincing.